The epidemiology of inflammatory bowel disease: East meets west - Mak, Wing Yan; Zhao, Mirabella; Ng, Siew Chien; Burisch, Johan (Journal of gastroenterology and hepatology, 2020)
The incidence of inflammatory bowel diseases (IBD) in East has risen over the past decade to become a global disease. The increasing number of studies on the incidence and course of IBD in East has enabled us to explore East versus West differences in the epidemiology of IBD which could enhance our understanding of the heterogeneity of the disease and eventually assist in the discovery of novel therapeutic targets and design of preventive strategies. Comparison of population‐based data in East and West reveals that the incidence of IBD has risen rapidly in East while plateauing in West. Furthermore, the clinical presentation and course of IBD differs between East and West with more patients in East presenting with complicated disease. Considering the scarcity of population‐based data from East and the lack of studies with long durations of follow‐up, it remains to be clarified whether these differences reflect true differences in disease presentation. The effects of genetic and environmental risk factors contributing to IBD also differ between Eastern and Western populations. Considering the differential effects of genetic and environmental risk factors in East and West, future studies should seek to discover novel genetic and environmental risk factors which might specifically apply to eastern populations. In this narrative review, we compare the epidemiology of IBD between eastern and western countries by summarizing evidence from population‐based cohort studies in the last ten years. Furthermore, we look at differences in genetic susceptibility and environmental triggers of IBD between East and West.